Contagious Representation : Women's Political Representation in Democracies around the World - Thames, Frank; Williams, Margaret S. (Margaret Susan) (Book collections on Project MUSE., 2013)
"Women's participation in parliaments, high courts, and executive offices worldwide has reached record high numbers, but this global increase in women's representation masks significant variation among different democratic political systems. For example, in December of 2009, Rwanda's legislature contained 56% women, while the U.S. Congress contained only about 17% and the Japanese Diet had only 11%. Since 2000, only twenty-seven women have achieved executive office worldwide. Contagious Representation is a comprehensive look at women's participation in all aspects of public life in the main democratic political institutions--the executive, the judiciary, the legislature, and within political parties. Moving beyond studies of single countries and institutions, Contagious Representation presents original data from 159 democratic countries spanning 50 years, providing a comprehensive understanding of women in democracies worldwide. The first volume to offer an analysis on all avenues for women's participation for such a lengthy time period, Contagious Representation examines not only the causes of women's representation in the main democratic political institutions but also how women's representation in one institution affects the others. Each chapter contains case studies and examples of the change in women's participation over time from around the world. Thames and Williams definitively explain the rise, decline, or stagnant levels of women's political participation, considering how representation is contagious across political institutions and gaining a better understanding of what factors affect women's political participation"--